M94 as a Unique Testbed for Black Hole Mass Estimates and AGN Activity at Low Luminosities - Anca Constantin; Anil C. Seth (Advances in Astronomy)
We discuss the peculiar nature of the nucleus of M94 (NGC 4736) in the context of new measurements of the broad Hα emission from HST-STIS observations. We show that this component is unambiguously associated with the high-resolution X-ray, radio, and variable UV sources detected at the optical nucleus of this galaxy. These multiwavelength observations suggest that NGC 4736 is one of the least luminous broad-line (type 1) LINERs, with Lbol=2.5×1040 erg s-1. This LINER galaxy has also possibly the least luminous broad-line region known (LHα=2.2×1037 erg s-1). We compare black hole mass estimates of this system to the recently measured ∼7×106 M⨀ dynamical black hole mass measurement. The fundamental plane and M-σ* relationship roughly agree with the measured black hole mass, while other accretion-based estimates (the M-FWHM(Hα) relation, empirical correlation of BH mass with high-ionization mid-IR emission lines, and the X-ray excess variance) provide much lower estimates (∼105 M⨀). An energy budget test shows that the AGN in this system may be deficient in ionizing radiation relative to the observed emission-line activity. This deficiency may result from source variability or the superposition of multiple sources including supernovae.